Short-term efficacy of stenting as a rescue therapy for acute atherosclerotic occlusion in anterior cerebral circulation - Wang, Jianyi; Shang, Suhang; Dun, Wanghuan; Chen, Chen; Gao, Fan; Yu, Jia; Han, Jianfeng; Liu, Fude (Frontiers in Neurology, 2023)
Purpose To explore the efficacy and safety of Neuroform EZ stent in treating acute anterior circulation large artery occlusion.To retrospectively analyze the clinical data of 42 consecutive patients with acute anterior circulation large atherosclerotic occlusion who were treated with Neuroform EZ stent from January 2018 to August 2019 in our stroke care center, including baseline characteristics, images, therapeutic condition, and follow-up data.Results There were 42 MT failure cases of intracranial atherosclerotic stenosis with rescue Neuroform EZ stent implantation, of which 78.6% (33/42) had a good prognosis and 88.1% (37/42) showed no re-stenosis at follow-up. The average time from puncture to recanalization is 79.50±14.19min. The successful rate of intraoperative stent release is 97.6%, while there is 1 case of stent displacement and 3 cases of thrombus escape, and 6 cases of hemorrhage.Rescue therapy of Neuroform EZ stent for acute anterior circulation large atherosclerotic occlusion can archive good short-term imaging and clinical results, while long-term follow-up is still needed to verify. Recently, multiple landmark trials((MR CLEAN, ESCAPE, SWIFT PRIME, REVASCAT, and EXTEND IA) indicated that endovascular therapy advances over the best medical treatment for patients exhibited with acute ischemic stroke caused by large